1995
DOI: 10.1147/rd.391.0167
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of IBM CMOS DRAM technology

Abstract: The development of DRAM at IBM produced many novel processes and sophisticated analysis methods. Improvements in lithography and innovative process features reduced the cell size by a factor of 18.8 in the time between the 4Mb and 256Mb generations. The original substrate piate trench cell used in the 4Mb chip is still the basis of the 256Mb technology being developed today. This paper describes some of the more important and interesting innovations introduced in IBM CMOS DRAMs. Among them, shallow-trench isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Some DRAM manufacturers use polysilicon filled trench capacitor as a storage node (2). In this case, polysilicon recess processes play an important role in the overall process flow.…”
Section: Polysilicon Recess In Dram Trench Capacitorsmentioning
confidence: 99%
“…Some DRAM manufacturers use polysilicon filled trench capacitor as a storage node (2). In this case, polysilicon recess processes play an important role in the overall process flow.…”
Section: Polysilicon Recess In Dram Trench Capacitorsmentioning
confidence: 99%
“…GIDL is induced by band-to-band tunneling effect in strong accumulation mode and generated in the gate-to-drain overlap region. This leakage current component has been observed in DRAM trench transistor cells and in EEPROM memory cells and is identified as the main leakage mechanism of discharging the storage nodes in sub-micron dynamic logic [1][2][3]. This paper presents test results of abnormally high leakage current (∼0.1 -1 mA) observed in a digital ASIC.…”
Section: Introductionmentioning
confidence: 88%
“…al. [1] suggested that the poly-silicon line should have finite spacing from this interface ( Figure 5). …”
Section: Leakage Current At Locos Isolation Edgementioning
confidence: 99%
“…Among many known lealcage currents, the junction leakage current from the storage node is known to be the major leakage mechanism [12]. Due to local process variations, It varies among cells, resultmg in fluctuations oft RET among the cells [15,5]. Studies have showed that the log^itREr) of the cells follows a bimodal distribution, akin to the one shown in Figure 1.…”
Section: N Refresh In Conventional Drammentioning
confidence: 99%